Product Innovation, Partnerships, Market Orientation, and Footwear SME Performance: The Mediating Role of Marketing Strategy - Keni Kaniawati; Nurul Hermina; Yani Iriani (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
Small and Medium Enterprises (SMEs) in the footwear sector face increasing competitive pressure from imported products, rapidly changing fashion trends, shifting consumer preferences, and the growth of digital purchasing behavior. These challenges require footwear SMEs not only to innovate and build partnerships, but also to translate market knowledge and internal capabilities into effective marketing strategies. This study examines the mediating role of marketing strategy in the relationship between product innovation, business partnerships, market orientation, and marketing performance. A quantitative explanatory approach with a cross-sectional design was employed. Data were collected from 310 footwear SME owners or managers in the Greater Bandung area using proportional random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that product innovation (β = 0.312), business partnerships (β = 0.281), and market orientation (β = 0.410) have significant positive effects on marketing strategy, with market orientation emerging as the strongest predictor. Marketing strategy also has a significant positive effect on marketing performance (β = 0.550) and significantly mediates the relationships between the three antecedents and marketing performance. This study contributes to SME marketing literature by demonstrating that marketing strategy functions as an implementation mechanism that converts innovation, collaboration, and market intelligence into performance outcomes in a trend-sensitive footwear industry. Practically, the findings suggest that footwear SMEs should prioritize market intelligence, align product innovation with fashion trends and customer value, and develop partnerships that strengthen distribution, digital promotion, and market access. These elements should be integrated into consistent segmentation, positioning, and offline–digital channel strategies to improve marketing performance.